Les effets de la dimension relationnelle dans la relation pédagogique de direction de mémoire en Master - Laetitia Gérard (Nantes Université, 2012)
Master's level dissertation supervision is one of the characteristics differentiating graduate-level (Master's) learning structures from learning structures at the undergraduate level (Bachelor's) It represents a new two-way relationship for students which differs from the group learning relationship they had experimented with up until the end of their undergraduate studies. This study is primarily interested in the interpersonal relationship within the supervisor-student pair, which supports the development of the initial professional supervisory relationship.Semi-directive interviews were conducted to collect data on the actors' (master's students and their supervisors) perceptions of the supervisory relationship.The results show that the interpersonal relationship can have positive but also negative effects on the hands-on research training of master's level research apprentices. The data highlight strategies used by supervisors to maintain a relational distance that is beneficial to their students' scientific training.